Change and Continuity in the 2016 and 2018 Elections - Aldrich, John (SAGE Publications, 2019)
This text meticulously and accessibly explains the National Election Studies data and analyzes its importance and impact, covering the most recent presidential and Congressional elections, voter turnout, and the social forces, party loyalties, and prominent issues that affect voting behavior.